Morphometric Study of Suprascapular Notch and Scapular Dimensions in Ugandan Dry Scapulae with Specific Reference to The Incidence of Completely Ossified Superior Transverse Scapular Ligament - Adewale, Adesanya Olamide; Monima, Ann Lemuel; Kasozi, Keneth Iceland; Nalugo, Halima; Ssempijja, Fred (BMC musculoskeletal disorders, 2020)
Understanding of suprascapular notch (SSN) anatomy and relationship with scapular dimensions are vital in diagnosis, prevention, and assessment of suprascapular nerve entrapment syndrome. The study aimed to assess morphometry of suprascapular notch and scapular dimensions in Ugandan dry scapulae with specific reference to scapulae with completely ossified superior transverse scapular ligaments. This was a cross-sectional analytical study conducted on 50 Ugandan dry scapulae. SSN types and prevalence of completely ossified superior transverse scapular ligament among dry scapulae were quantified and compared with previous data. Scapular dimensions were assessed by measuring scapular length (A), scapular width (B), glenoid length (C), and glenoid width (D). One-way ANOVA was used to compare scapular dimensions of scapulae with different SSN types, and Spearman’s correlation coefficient was used to evaluate the correlation coefficient of scapular dimensions amongst groups. Superior transverse scapular ligament (STSL) was completely ossified in 8% of cases. There was no significant (P > 0.05) difference between scapular dimensions of scapulae with completely ossified STSL compared to scapulae with other SSN types. Scapulae with completely ossified STSL showed strong negative (r = − 0.89137, r = − 0.877) correlations for its A, B respectively compared against D, this finding was not true to scapulae of other SSN types. Also, there were strong positive or negative (r > 0.7, r > − 0.7) correlations: for A, types I and III compared to type VI; for B, types I, III compared to VI; for C, type IV and VI; and for D, type III and VI. The prevalence of completely ossified STSL is moderately high in the Ugandan population. Characteristics of the scapula (scapular dimensions) are not ‘vital’ but rather important or relevant for shoulder pathology with specific reference to suprascapular nerve entrapment syndrome due to completely ossified superior transverse scapular ligaments. Further correlation analyses of scapular dimensions of different SSN types in different populations are important.
Keywords: Suprascapular notch, Completely ossified superior transverse scapular ligament, Scapular dimensions, Suprascapular nerve entrapment syndrome, Anatomical variation, Ugandan population